2000
DOI: 10.1007/s001340000603
|View full text |Cite
|
Sign up to set email alerts
|

Do we need new indications for ECMO in neonates pretreated with high-frequency ventilation and/or inhaled nitric oxide?

Abstract: For neonates pretreated with HFV/iNO, an OI > 40 is an inadequate ECMO indication. Based on our data we hypothesize that an OI > or = 25 after 72 h of HFV/ iNO is a better ECMO indication that avoids prolonged barotrauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…We consider it more likely that the reduction in OI reflects the increased use of iNO and HFOV, and that the babies needing ECMO support in the current era, were in fact sicker than those needing ECMO 10 years ago. Indeed some authors have suggested that the improvement in oxygenation observed with iNO should be used as a window for safer ECMO cannulation and that neonates treated with HFOV and iNO should be considered for ECMO at a lower OI than those treated conventionally 9 14…”
Section: Discussionmentioning
confidence: 99%
“…We consider it more likely that the reduction in OI reflects the increased use of iNO and HFOV, and that the babies needing ECMO support in the current era, were in fact sicker than those needing ECMO 10 years ago. Indeed some authors have suggested that the improvement in oxygenation observed with iNO should be used as a window for safer ECMO cannulation and that neonates treated with HFOV and iNO should be considered for ECMO at a lower OI than those treated conventionally 9 14…”
Section: Discussionmentioning
confidence: 99%
“…The oxygenation index and other severity of illness criteria are limited in their ability to predict mortality, 9 particularly as the non-ECMO management of neonates with respiratory failure has evolved. These severity of illness criteria for ECMO may need to be updated, 10, 11, 12, 13 particularly for neonates with CDH, 14, 15, 16 but at the moment are fairly well standardized.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK trial, the control group had a mortality rate, depending on the underlying disease, of 43% in meconium aspiration syndrome to 100% in congenital diaphragmatic hernia. To avoid a delay in the use of ECMO because of an inadequate response to prior iNO treatment and other techniques like HFO, it has been suggested to lower the current ECMO criteria in patients suffering from severe hypoxic respiratory failure, who are already treated with iNO and HFO ventilation [2,9]. Schumacher et al [10] showed a shorter length of hospitalization, better cost-effectiveness and better (neurological) outcome at 1 year of age when neonates were randomized to lower threshold criteria to initiate ECMO.…”
Section: Cerebral Aspects Related To Neonatal Ecmomentioning
confidence: 99%